THE ANALYSIS OF STUDENTS’ DIFFICULTIES IN COMPREHENDING TOEFL READING TEXT AT ISLAMIC UNIVERSITY OF OGAN KOMERING ILIR KAYUAGUNG - Eka Mahendra; Dewi sartika; Eva Saptarina (Edu-Ling: Journal of English Education and Linguistics, 2020)
The objective of this research is to find the difficult skills in TOEFL reading text faced by the students of English Language Education Study Program of Islamic University of Ogan Komering Ilir Kayuagung. The subject of this research was students English Department Isalamic University Ogan Komering Ilir To conduct this study, the descriptive qualitative was used. To collect the data, TOEFL reading test and interview were used. To analyze the data, data reduction, data display, and drawing conclusion or interpretation. The result of the study showed that students had difficulty finding main idea questions (66.6%), organization ideas (72%), stated detail question (60%), unstated detail question (62%), implied detail question (75%), transition question (74%), reference (56%), vocabulary (54.5%), question about where in the passage (55%), and tone purpose (63%). It was happened because most of the students did not like reading scientific text, had low motivation, and had limitation vocabulary.